Early evolution of the lungfish pectoral-fin endoskeleton: evidence from the Middle Devonian (Givetian) Pentlandia macroptera - Jude, Emma; Johanson, Zerina; Kearsley, Anton; Friedman, Matt (Frontiers in Earth Science, 2014)
As the closest living relatives of tetrapods, lungfishes are frequently used as extant models for exploring the fin-to-limb transition. These studies have generally given little consideration to fossil taxa. This is because although lungfish fins are relatively common in the fossil record, the internal structure of these fins is virtually unknown. Information on pectoral-fin endoskeletons in fossil representatives of Dipnomorpha (the lungfish total group) is limited to poorly preserved remains in the lungfish Dipterus and Conchopoma and more complete material in the porolepiform Glyptolepis. Here we describe a well-preserved pectoral-fin endoskeleton in the Middle Devonian (Givetian) lungfish Pentlandia macroptera from the John O’Groats fish bed, Caithness, northeastern Scotland. The skeleton is in association with a cleithrum and clavicle, and consists of a series of at least eight mesomeres. Extensive series of preaxial and postaxial radials are present. Some of the radials are jointed, but none branch. No mesomere articulates with multiple radials on either its pre- or post-axial face. The first two mesomeres, corresponding to the humerus and ulna, bear well-developed axial processes. Uniquely among dipnomorphs, a distinct ossification centre corresponding to the radius is present in Pentlandia. A review of anatomy and development of the pectoral-fin endoskeleton in the living Neoceratodus is presented based on cleared and stained material representing different size stages. These developmental data, in conjunction with new details of primitive lungfish conditions based on Pentlandia, highlight many of the derived features of the pectoral-fin skeleton of Neoceratodus, and clarify patterns of appendage evolution within the dipnomorphs more generally.